Assessment of quality of life after hysterectomy using european quality of life five dimension scale (EQ5D) - Parveen Rajora; Deeksha Sharma; Gaganpreet Singh; Prabhleen Kaur; Anisha Galhotra; Arnav Galhotra (Wolters Kluwer Medknow Publications, 2023)
In several regions throughout the globe, caesarean sections constitute the most common nonobstetric surgery, followed by hysterectomy, which is the surgical excision of the uterus. While it is not the only solution for reproductive organ issues, it is the most effective technique to treat many illnesses over the long term. The uterus is a very critical reproductive organ for all age groups as this is not only essential for giving birth but also for hormonal-related physiology in women's life. The quality of life is impacted by a number of hysterectomy-related effects on females. Physical, psychological, environmental, and social relations are some of these impacts. All EuroQol five-dimensions (EQ5D) subscales significantly improved, as per the research 's findings. Preoperative psychosocial status, perioperative pain, indication of hysterectomy, complications occur during surgery, and mode of hysterectomy postoperative infection had been discovered as determinants of quality of life outcome following hysterectomy. In most of the subjects we noticed small, however, noticable improvements in all component of EQ5D Scale. The strengths of EQ5D questionnaire lie in its simplicity and moreover it is available in several languages.